Kisspeptin-mediated improvement of sensitivity to BRAF inhibitors in vemurafenib-resistant melanoma cells - Guzzetti, Carlotta; Corno, Cristina; Vergani, Elisabetta; Mirra, Luca; Ciusani, Emilio; Rodolfo, Monica; Perego, Paola; Beretta, Giovanni L. (Frontiers in Oncology, 2023)
Metastatic dissemination is still one of the major causes of death of melanoma's patients. KiSS1 is a metastasis suppressor originally identified in melanoma cells, known to play an important physiological role in mammals' development and puberty. It has been previously shown that expression of KiSS1 could be increased in lung cancer cells using epigenetic agents, and that KiSS1 could have a pro-apoptotic action in combination with cisplatin. Thus, the aim of the present study was to examine in human melanoma vemurafenib sensitive and -resistant BRAF mutant cells characterized by different mutational profiles and KiSS1, KiSS1 receptor and KiSS1 drug-induced release, if peptides derived from KiSS1 cleavage, i.e., kisspeptin 54 could increase the sensitivity to vemurafenib of human melanoma vemurafenib sensitive and -resistant cells, using cellular, molecular and biochemical approaches. We found that kisspeptin 54 increases vemurafenib pro-apoptotic activity in a statistically significant manner, also in drug resistant cellular models. The efficacy of the combination appears to reflect the intrinsic susceptibility of each cell line to PLX4032-induced apoptosis, together with the different mutational profile as well as perturbation of proteins regulating the apoptotic pathway, The results presented here highlight the possibility to exploit KiSS1 to modulate the apoptotic response to therapeutically relevant agents, suggesting a multitasking function of this metastasis suppressor.